Stalin and the german invasion of Russia 1941 : a failure of reasons of state? - Haslam, Jonathan (2000)
Comenta la obra de Gabriel Gorodetsky
Keywords: Gorodetsky, Gabriel; Ocupación militar; Alemania; Rusia; Guerra